1999
DOI: 10.1109/17.740041
|View full text |Cite
|
Sign up to set email alerts
|

Occupational cultures as a challenge to technological innovation

Abstract: This paper explains conflict over technological process innovation in cultural terms, drawing primarily on a case study of electric power distribution and strategies to automate its operation. The paper shows how different occupational cultures, "operators" and "engineers," use different mental models or cognitive representations of technology that are adaptive to their particular work contexts, but which give rise to conflicting evaluations of technological innovation. While these cultural groups may be motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…A key issue that needs to be addressed when looking at ways to represent knowledge lies in the fact that different people, and in particular people with different educational and occupational backgrounds, have different ways to represent knowledge, which are adaptive to the knowledge manipulations needs of their occupations (e.g., Dougherty, 1992;von Meier, 1999;D'Adderio, 2003). 'Pragmatic' approaches have been particularly effective in investigating the properties of objects that mediate problem-solving activities requiring the collaboration of individuals with different objectives and ways of framing problems.…”
Section: Objects Of Memorymentioning
confidence: 99%
“…A key issue that needs to be addressed when looking at ways to represent knowledge lies in the fact that different people, and in particular people with different educational and occupational backgrounds, have different ways to represent knowledge, which are adaptive to the knowledge manipulations needs of their occupations (e.g., Dougherty, 1992;von Meier, 1999;D'Adderio, 2003). 'Pragmatic' approaches have been particularly effective in investigating the properties of objects that mediate problem-solving activities requiring the collaboration of individuals with different objectives and ways of framing problems.…”
Section: Objects Of Memorymentioning
confidence: 99%
“…One stream of such studies focuses on the relationship between organizational culture and IT adoption [58][59][60][61][62][63]. For example, Hoffman and Klepper [60] found that organizations with mercenary cultures (i.e., low in sociability and high in solidarity) perform better than organizations with more networked cultures (i.e., high sociability and low solidarity) in technology assimilation.…”
Section: Organizational Culture Theorymentioning
confidence: 99%
“…Tan et al has compared the predisposition of people to report bad news in software projects and documented the moderating effect of national culture on organizational climate (whether reporting bad news results in reward or punishment) and information asymmetry (whether hiding bad news is feasible over time) [62]. At the level of communities of practice, Meier has drawn attention to the need for management to take occupational cultures into account when planning technological innovation; conflicts may otherwise arise due to different mental models or cognitive representations of technology [43]. At the level of organizational cultures and subcultures, Huang et al have shed light on how cultural variations during implementation of company-wide information systems may challenge knowledge sharing and collaboration among groups [25].…”
Section: Culture In Spimentioning
confidence: 99%